Expansion of Commercial Sugarcane Cultivation among Smallholder Farmers in Uganda: Implications for Household Food Security - Mwavu, Edward N.; Kalema, Vettes K.; Bateganya, Fred; Byakagaba, Patrick; Waiswa, Daniel; Enuru, Thomas; Mbogga, Michael S. (Land, 2018)
Understanding the impact of commercial agriculture in the face of global change is critical to support strategies that ensure food security and alleviate poverty among households. We assessed the contribution of commercial sugarcane cultivation to household-level food security among smallholder farmers in Busoga sub-region, eastern Uganda. Land use changes are motivated by quick commercial gains rather than sustained food production; a situation that influences food security. The majority of households cultivate few crop varieties, lack adequate and nutritious foods, and have inadequate income to purchase food to meet their needs. Inadequacy of food within some commercial sugarcane-cultivating households suggests that generating income does not necessarily increase food security. To cope with food insecurity, households offer labour in exchange for food, borrow food, ration food, and at times steal. This is exacerbated by increasing food crop failures, large family sizes, trade in food items, and declining availability of food and land for food production. Commercial sugarcane cultivation is the main driver of food insecurity but given its perceived economic benefits, future sugarcane plantations expansion in the region is probably inevitable. Therefore, future policy should be designed to provide triple-win strategies (i.e., food security, poverty alleviation, and climate change adaptation) that provide sustainable livelihoods.
Keywords: Poverty alleviation; Sustainable livelihoods; Climate change; Commercial agriculture